2015
DOI: 10.1001/jamapsychiatry.2015.0505
|View full text |Cite
|
Sign up to set email alerts
|

Two Patterns of White Matter Abnormalities in Medication-Naive Patients With First-Episode Schizophrenia Revealed by Diffusion Tensor Imaging and Cluster Analysis

Abstract: IMPORTANCE Accumulating evidence supports the hypothesis that cerebral white matter abnormalities are involved in the pathophysiology of schizophrenia; however, findings from in vivo neuroimaging studies have been inconsistent. Besides confounding factors, including age, illness duration, and medication effects, an additional cause for the inconsistent results may be heterogeneity in the nature of white matter alterations associated with the disorder.OBJECTIVE To investigate whether different patterns of white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 57 publications
7
81
0
Order By: Relevance
“…According to the macrocircuit theory, specific white matter tracts are disrupted either as a cause or a consequence of a disorder in the gray matter regions they connect. Consistent with previous reports, the current study also found moderate correlations between the severity of negative symptom and diffusion measurements of certain tracts, including FMAJ, FMIN, SLF, and ILF [43]. …”
Section: Results Of Human Brain Datasupporting
confidence: 92%
See 1 more Smart Citation
“…According to the macrocircuit theory, specific white matter tracts are disrupted either as a cause or a consequence of a disorder in the gray matter regions they connect. Consistent with previous reports, the current study also found moderate correlations between the severity of negative symptom and diffusion measurements of certain tracts, including FMAJ, FMIN, SLF, and ILF [43]. …”
Section: Results Of Human Brain Datasupporting
confidence: 92%
“…The FMIN linking DLPFC region is traversed by tracts interconnecting the frontal lobe, providing evidence for disrupted anatomical connections in the fronto-limbic circuitry [43]. FA changes in the SLF, the major white matter connection between prefrontal and parietal cortices, relate to verbal working memory performance [17].…”
Section: Results Of Human Brain Datamentioning
confidence: 99%
“…This is notable considering that RDoC and ROAMER emphasize stratification on the basis of mappings between biological systems and cognitive domains, not just symptoms (10). To date, few studies have stratified psychiatric disorders on the basis of quantitative biological measures, and these studies have predominantly used neuroimaging-based measures (13, 16, 17, 52). This may be because of well-known problems with clustering complex, high-dimensional data (see Advantages and Disadvantages of Clustering).…”
Section: Applications To Stratify Psychiatric Disordersmentioning
confidence: 99%
“…Thus, an alternative approach resolving the heterogeneity with neurobiologic parameters, such as anatomic and functional imaging features, may represent an advantageous strategy to identify subgroups of patients, after which the clinical dimensions of these subgroups in terms of symptoms and treatment response to different therapies can be examined. Recently, Sun et al (108) have used a data-driven patient-clustering method to identify two distinct patterns of white matter abnormalities in the early phase of schizophrenia, suggesting qualitatively distinct genetic influences or neurodevelopmental alterations. This…”
Section: State Of the Art: Psychoradiologymentioning
confidence: 99%